2017
DOI: 10.1007/s00405-017-4837-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intraoperative bradycardia during ear, nose, throat and maxillofacial surgery

Abstract: Intraoperative bradycardia (IOB) is one of the most common cardiac arrhythmias observed in clinical anaesthetic practice. Controlled hypotension, as a strategy of lowering patient's blood pressure during anesthesia has been practiced for decades in head and neck surgery. The aim of our study was to determine the incidence and the risk factors for intraoperative bradycardia in maxillofacial, ear, nose and throat surgery, as well as to determine whether controlled hypotension affects the occurrence of IOB. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In head and neck surgery, autonomic reflexes such as direct vagal stimulation, TCR or baroreceptor reflex can cause severe bradycardia, even cardiac arrest [4]. The most common cause of intraoperative bradycardia is a drug event [8]. However, in present case, the depth of anesthesia was maintained properly at BIS www.anesth-pain-med.org Cambell et al [11] reported cases of cardiac arrest and bradycardia associated with maxillectomy in 1994.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In head and neck surgery, autonomic reflexes such as direct vagal stimulation, TCR or baroreceptor reflex can cause severe bradycardia, even cardiac arrest [4]. The most common cause of intraoperative bradycardia is a drug event [8]. However, in present case, the depth of anesthesia was maintained properly at BIS www.anesth-pain-med.org Cambell et al [11] reported cases of cardiac arrest and bradycardia associated with maxillectomy in 1994.…”
Section: Discussionmentioning
confidence: 72%
“…The causes of intraoperative bradycardia include drug events, airway and ventilation problems, autonomic reflexes, and epidural anesthesia or spinal anesthesia [8]. In head and neck surgery, autonomic reflexes such as direct vagal stimulation, TCR or baroreceptor reflex can cause severe bradycardia, even cardiac arrest [4].…”
Section: Discussionmentioning
confidence: 99%
“…19 However, there are other factors related to bradycardia such as the use of remifentanil (vagus-related bradycardia), patients older than 50 years, and ear, nose, throat/maxillofacial surgery, with particular attention to ear surgery. 20 However, it is challenging to determine precisely the cause of these episodes during the surgery. In our cohort, those 6 patients affected were older than 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] It was reported that the incidence of bradycardia during otolaryngology surgery is 20.5%. [5] Opioids have been used for analgesia in laryngeal microsurgery. [6-8] However, in view of their pharmacological effects on autonomic function, the use of vagotonic opioids such as fentanyl and its derivatives may lead to bradycardia.…”
Section: Introductionmentioning
confidence: 99%